Psychometric Properties of Research Competency Scales: A Systematic Review - Tapullima-Mori, Calixto (2023)
The study aimed to explore the psychometric properties of research competency scales published in the scientific literature in seven databases: Scopus, Web Of Science, ERIC, Embase, EBSCO, PubMed and SciELO between 2014 and June 2023. Thirteen papers were systematized, where 11 scales were found that measured content validity using indexes such as the S-CVI, Aiken's V and item-test correlations. Similarly, the results of the exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) presented adequate fit indices such as CFI, GFI, TLI, SRMR and RMSEA, which validated the factor structure. Reliability was mostly evaluated through Cronbach's Alpha coefficient, yielding high and consistent values. In addition, coefficients such as McDonald's Omega, ordinal Omega, Guttman and Spearman Brown have been used, all reflecting a value above .70 and internal consistency in the measurements. In synthesis, instruments such as the RCS, SRCS, RPCS, SPRDS, EAHIF, AHABI, ERL, self-perception questionnaires and rubrics have proven to be effective tools in the assessment and development of research skills. In that sense, these scales can improve the assessment and development of research skills in university students, and it is expected that future research will use them to evaluate pedagogical approaches and international contexts.